1912 La. Acts 505 - (:unkn) unknown (My University, 1912)
Twenty-fifth: To regulate the buying, caring, storing, selling and using of gun powder and fire crackers, and fireworks manufactured or prepared therefrom, and all other combustible or explosive substances, the exhibition of fireworks, the discharge of firearms and the lights, in barns, stables and other buildings, and restrain the making of bonfires at any place within the limits of the city.
Keywords: TRANSFER, MANUFACTURE & STORAGE OF GUNPOWDER